2017
DOI: 10.3390/su9071214
|View full text |Cite
|
Sign up to set email alerts
|

Measures of a Sustainable Commute as a Predictor of Happiness

Abstract: Abstract:The ways in which we travel-by what mode, for how long, and for what purpose-can affect our sense of happiness and well-being. This paper assesses the relationships between measures of the sustainability of transportation systems in U.S. metropolitan areas and subjective well-being. Associations between self-reported happiness levels from the Gallup Healthways Well-being Index and commute data were examined for 187 core-based statistical areas (CBSA). We also supplement this quantitative analysis thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Prior research also indicates that sustainability’s influence on subjective well‐being is an area where future research is particularly needed to show personal outcomes for sustainable behaviors that consumers may otherwise not feel incentivized to join (Paralkar, Cloutier, Nautiyal, & Mitra, ). Building off prior research in examining community‐level measures of sustainable behavior (Cloutier et al, ; Paralkar et al, ), we expect that individual‐level sustainable consumption practices will positively lead to subjective well‐being.
H3 Participation in sustainable consumption practice s positively correlates with consumers’ subjective well‐being .
…”
Section: Religion’s Influence On the Sustainable Consumptionmentioning
confidence: 89%
See 2 more Smart Citations
“…Prior research also indicates that sustainability’s influence on subjective well‐being is an area where future research is particularly needed to show personal outcomes for sustainable behaviors that consumers may otherwise not feel incentivized to join (Paralkar, Cloutier, Nautiyal, & Mitra, ). Building off prior research in examining community‐level measures of sustainable behavior (Cloutier et al, ; Paralkar et al, ), we expect that individual‐level sustainable consumption practices will positively lead to subjective well‐being.
H3 Participation in sustainable consumption practice s positively correlates with consumers’ subjective well‐being .
…”
Section: Religion’s Influence On the Sustainable Consumptionmentioning
confidence: 89%
“…In sum, a broader model is proposed where religiosity influences sustainable consumption, which then influences consumer well‐being. This expectation follows the connection between religiosity and sustainable consumption, as discussed in support for H1 (cf., Leary et al, ; Minton et al, ) and H2 (cf., Minton, ; Wolkomir et al, ), as well as sustainable consumption’s positive connection with subjective well‐being, as discussed in support for H3 (cf., Cloutier et al, ; Dunn et al, ; Paralkar et al, ,). With this mediating expectation, we acknowledge that many other mediators likely exist between religiosity and consumers’ subjective well‐being (e.g., integration in a social network, decreased participation in risky behaviors, altered views of anxiety or stress producing situations).…”
Section: Religion’s Influence On the Sustainable Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicators mainly focus on psychological aspects that possess an intrinsically intangible essence and tend to come up the side the well-known environmental, social, and economic dimensions of sustainability. In other words, feelings as satisfaction, personal well-being, intrinsic motivation, and happiness (Kaiser, 1998;Iwata, 2001;Kasser, 2009, Rojas, 2011Cloutier, Karner, Breetz, Briggs, & Carlson, 2017) play a fundamental role in developing sustainability and promoting sustainable development. Some studies have found the relevance of the concept of "justice," in terms of impartial treatment and compensation.…”
Section: Psychological Issuesmentioning
confidence: 99%
“…Individuals that practice eco-friendly behaviors are happier than individuals that are not considerate of green aspects (Brown &Kasser, 2005;Turcotte, 2006;O'Brien, 2013;Barrington, 2016). In this scenario, happiness represents the contemporary antecedent of pro-environmental behavior (Cloutier et al, 2017) and a consequence of sustainable practices (Kasser, 2009) converging to achieve general well-being (Helne & Hirvilammi, 2015). In recent years, due to the escalating interest in happiness, several studies have aimed to lead people and organizations to find the "good life," achievable whether and when sustainability is partnered with well-being and happiness, creating what scholars label as "sustainable happiness" (O'Brien, 2008;2013), that is "the pursuit of happiness that does not exploit other people, the environment or future generations" (O'Brien, 2008).…”
Section: Psychological Issuesmentioning
confidence: 99%